Penafsiran HR. Muslim dalam Lagu Gala Bunga Matahari: Analisis Hermeneutika Hans-Georg Gadamer - Ubay Abdillah Muhammad; Muhid (Jurnal Ilmiah Ilmu Ushuluddin, 2024)
This study examines the interpretation of a hadith narrated by Muslim within Sal Priadi’s song “Gala Bunga Matahari” through the lens of Hans-Georg Gadamer’s hermeneutics. The primary focus is to explore how the song’s lyrics reflect the spiritual values embedded in the hadith and their relevance in contemporary life. The song conveys themes of longing, loss, and the hope of reunion with a loved one, employing the sunflower as a symbolic representation of happiness and warmth. Utilizing a descriptive qualitative approach, the analysis investigates the interaction between the textual meaning of the hadith and the artistic elements of the song. The findings indicate that the lyrics may serve as an effective medium for transmitting moral and spiritual messages to younger generations, who are more deeply engaged with entertainment media. Through the dialogical process between the listeners’ personal experiences and the meaning of the lyrics, the study underscores the importance of a profound understanding of hadith in addressing present-day social challenges. These findings not only contribute to interpretive studies in the field of hadith but also enrich the discourse on how Islamic teachings can be actualized in daily life through the medium of music. Accordingly, the research highlights both the enduring relevance of hadith in the modern era and the potential of music as a powerful instrument of da‘wah.